EFEITO DAS GIBERELINAS NO AMADURECIMENTO DO CAQUI â€œTAUBATÃ‰â€ (Diospyros kaki) - H., Marcel Awad; Amenomori, Hideki (REVISTA DE AGRICULTURA, 2016)
EFEITO DAS GIBERELINAS NO AMADURECIMENTO DO CAQUI â€œTAUBATÃ‰â€ (Diospyros kaki)